STUDI KEPATUHAN DAN KENDALA PAJAK BAGI INFLUENCER TIKTOK DI INDONESIA - Winda Alfitri Ayuhanas; Hastanti Agustin Rahayu (Jurnal Bisnis Terapan, 2025)
Digital transformation has given birth to new professions such as influencers, who earn income from endorsements, sponsorships, and content monetization on platforms such as TikTok. The increasing income of influencers makes taxation an important issue in the Indonesian tax system. However, many influencers still do not understand or ignore their tax obligations. This study aims to show the importance of tax for influencers as a form of individual responsibility and contribution to the country. In addition, applicable tax regulations, legal risks for non-compliance, and the effect of tax on endorsement prices and influencer business strategies are also discussed. The method used is qualitative with a normative and empirical legal approach. With this approach, it is hoped that it can provide a deeper understanding of the presence of tax among TikTok influencers and its impact on their business decisions in choosing collaborations, pricing strategies, and sustainable sources of income.